2019
DOI: 10.1242/jeb.197681
|View full text |Cite
|
Sign up to set email alerts
|

Shearing overbite and asymmetrical jaw motions facilitate food breakdown in a freshwater stingray, Potamotrygon motoro

Abstract: Many species of fish process their prey with cyclic jaw motions that grossly resemble those seen in mammalian mastication, despite starkly different tooth and jaw morphologies. The degree of similarity between the processing behaviors of these disparate taxa has implications for our understanding of convergence in vertebrate feeding systems. Here, we used XROMM (X-ray reconstruction of moving morphology) to investigate prey processing behavior of Potamotrygon motoro, the ocellate river stingray, which has rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The hypothesis of an asymmetrical tension–compression behaviour in tessellated cartilage has been demonstrated in computational studies incorporating varying degrees of tissue complexity ( e.g ., Liu et al ., 2010; Seidel et al ., 2019a), most recently in biomimicked digital models that also demonstrated that the skeletal composite's mechanical performance can be altered through simple structural changes to the tessellation ( e.g ., increasing the joint gap delaying collision of tesserae when the skeleton is loaded in compression; Figure 7f) (Jayasankar et al ., 2020). The compression–tension asymmetry hypothesized for tessellated cartilage would impart a constrained flexibility that could play a role in permitting dynamic feeding behaviours ( e.g ., Dean & Motta, 2004; Laurence‐Chasen et al ., 2019) and in the tissue's ability to resist damage. In general, the combination of a stiff outer cortex and a soft inner core will tend to ensure that higher stresses are concentrated more safely in the stiffer cortical/mineralized tissue rather than the softer core/unmineralized tissue (Ferrara et al ., 2011; Fratzl et al ., 2016; Liu et al ., 2010).…”
Section: Shark and Ray Tessellated Cartilagementioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis of an asymmetrical tension–compression behaviour in tessellated cartilage has been demonstrated in computational studies incorporating varying degrees of tissue complexity ( e.g ., Liu et al ., 2010; Seidel et al ., 2019a), most recently in biomimicked digital models that also demonstrated that the skeletal composite's mechanical performance can be altered through simple structural changes to the tessellation ( e.g ., increasing the joint gap delaying collision of tesserae when the skeleton is loaded in compression; Figure 7f) (Jayasankar et al ., 2020). The compression–tension asymmetry hypothesized for tessellated cartilage would impart a constrained flexibility that could play a role in permitting dynamic feeding behaviours ( e.g ., Dean & Motta, 2004; Laurence‐Chasen et al ., 2019) and in the tissue's ability to resist damage. In general, the combination of a stiff outer cortex and a soft inner core will tend to ensure that higher stresses are concentrated more safely in the stiffer cortical/mineralized tissue rather than the softer core/unmineralized tissue (Ferrara et al ., 2011; Fratzl et al ., 2016; Liu et al ., 2010).…”
Section: Shark and Ray Tessellated Cartilagementioning
confidence: 99%
“…(2008) showed would tend to result in considerably lower stresses and higher strains than simulated shark jaws made of bone and subjected to the same bite forces (Figure 8). The hypothesized stress‐management behaviour of tessellated cartilage may therefore serve a protective function, in a skeletal tissue with limited or no healing capacity (Ashhurst, 2004; Dean et al ., 2017; Marconi et al ., 2020; Seidel et al ., 2016, 2017b), although it is surely loaded a large number of times over an animal's lifetime during cyclical swimming and feeding behaviours ( e.g ., Dean & Motta, 2004; Laurence‐Chasen et al ., 2019; Sasko et al ., 2006).…”
Section: Shark and Ray Tessellated Cartilagementioning
confidence: 99%
“…When LAR of the jaws is recorded in vivo it is associated with unfused symphyses of the jaws (e.g., Lieberman and Crompton 2000 ; Bhullar et al 2019 ; Laurence-Chasen et al 2019 ; Williams 2019 ). This association is limited in sample size, but consistent across a wide range of taxa and whereas prior studies measured LAR in vivo during food processing behaviors, this study extends the behavioral breadth of LAR to suction feeding.…”
Section: Discussionmentioning
confidence: 99%
“…LAR of vertebrate jaws is hypothesized to be a key factor in the feeding mechanisms of a variety of vertebrates ( Brainerd and Camp 2019 ). However, LAR of the jaws has only been documented in a handful of mammal taxa ( Kallen and Gans 1972 ; Oron and Crompton 1985 ; Bhullar et al 2019 ; Williams 2019 ), and in freshwater stingrays ( Potamotrygon motoro , Laurence-Chasen et al 2019 ). Jaw LAR has been hypothesized for anteaters ( Naples 1999 ), bats ( Kallen and Gans 1972 ), Tenrec ( Oron and Crompton 1985 ), a cichlid fish ( Aerts 1985 ), oceanic sharks ( Frazzetta and Prange 1987 ; Chappell and Seret 2021 ), and white spotted bamboo sharks ( Ramsay and Wilga 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation